(untitled) (GYMNASIUM, 2009)
The improvement of force-speed traits development methodology has been achieved based both on highest volume and on enhancement of all the performed exercises. Force-speed exercises have been enhanced by raising hurdles’ height, by increasing the bending angle of the gradient and the patches on which jumps have been performed, while the working volume has been adjusted to the age’s needs and abilities, as well as to the contest test specificity. Within the rates proposed by us, there can be found the following classes of means of technical and force-speed traits development: specific power exercises with weights, dynamic force exercises, force-speed exercises using hurdles and exercises to coordinate movements by muscles groups. Plyometrics exercises over fences that we have used contribute in developing the start power. Concentric and eccentric contractions contribute in the reactive power development. Within the power development program we have insisted on the quick and powerful application of force on the ground, having as purpose the recording of a maximum of motility units at the highest contraction speed.